Image Encryption Using Lorenz Chaotic System - Daniah Abul Qahar Shakir; Ahmad Salim; Seddiq Q. Abd Al-Rahman; Ali Makki Sagheer (Journal of Techniques, 2023)
In the age of the Internet, a lot of images are circulated among users, and some of these images contain financial or personal information that requires confidentiality. Encryption algorithms existed for a long time, and the data used was focused on the text data, while the multimedia data was neglected for a long time. In addition, there are significant shortcomings in 3D image coding techniques. This paper proposed a method for image encrypted and decrypted electronically using the Lorenz chaotic system, the supposed algorithm was developed by using the three equations of the Lorenz system, before that, the image pixels are destroyed using reversible shifting and rotating processes to increase the randomness of the encrypted pixels and thus the difficulty of cracking the cipher. Then he supposed technique gave the following results: The average entropy calculation was (7.285) before image encryption and (7.9974) after image encryption with an average NPCR of (99.65%) and UACI was (30.35%) this confirms that the proposed method is reliable and applicable. Moreover, the suggested technique gives the best outcomes when compared to other similar works.